"A watering of her desert": Depression and (Dis)consolation in Jenny Diski’s Monkey’s Uncle - Diane GAGNERET (E-REA)
Jenny Diski’s work has consistently offered a direct and daring exploration of many facets of human experience, including the most traumatic. Her 1994 novel Monkey’s Uncle, charting a middle-aged woman’s descent into depression following two cataclysmic events, qualifies as a work that seems all about inconsolability, yet invites a reflection on what David James calls “discrepant solace.” This paper will dwell on how contentious the notion of consolation reveals itself to be in a narrative which, steeped in experiences of loss and mourning, seems to foster disconsolation understood alternately as dismissal of, diversion from and reversal of expected consolatory practices and effects. To Diski’s protagonist, the loss of political ideals is more personal than the demise of her own child; the relentless despair experienced in depression becomes “a comforting trench into which she could curl safely” and no amount of therapy can match the obsessive reading of the book in which she immerses herself, and the readers. The novel may thus offer an exemplary case study in the art of (dis)consolation, suggesting that the comforting powers of uncomfortable stories should not be excluded from critical consideration.